In Vivo Gene Delivery by Lentiviral Vectors - Naldini, Luigi (Thrombosis and Haemostasis, 1999)
Successful gene therapy requires the efficient delivery and sustained expression of a therapeutic gene into the tissues of a human body. Most of the candidate tissues for therapeutic gene transfer are made of quiescent cells, such as from the brain, liver, and muscle. Thus, the optimal vector should infect nondividing cells, become stably associated with the genome of target cells, and support a high, steady-state level of transcription.1,2 Like all vectors derived from retroviruses, lentiviral vectors integrate into the chromatin of target cells and do not transfer any viral genes. Both of these features are important for achieving sustained expression of the transgene. Moreover, lentiviral vectors infect nondividing cells, a feature sharply distinguishing them from simple or onco-retroviral vectors.3 Upon infection, retroviruses deliver a nucleoprotein complex that reverse transcribes the viral RNA and integrates the newly made DNA into the chromatin. The nucleoprotein complexes of onco-retroviruses are excluded by the nucleus, and they reach the chromatin only when the nuclear membrane is fragmented during mitosis. This explains the dependence of a productive onco-retroviral infection on cell division occurring shortly after viral entry.4,5 In contrast, the nucleoprotein complexes of lentiviruses contain nuclear localization signals that mediate their active transport through the nucleopores during interphase. This explains the capacity of lentiviruses to infect macrophages, a nondividing cell type.6-9